P-89 Witnessing dying and distress: end-of-life care and the emotional impact on ambulance clinicians. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Murphy-Jones, Georgina; Catley, Karina
Abstract : Background: A two-year programme at a UK ambulance trust has been funded by Macmillan to improve the quality of care provided to end-of-life care patients. Ambulance clinicians manage intense emotions and family reactions during an end-of-life care crisis (Waldrop, Clemency, Lindstrom, Cordes, 2015), however, there is limited evidence that examines the emotional impact of such experiences. Aim: Examine the emotional impact of end-of-life care situations on ambulance staff. Methods: An electronic survey collected 258 responses from operational staff to identify support needs and inform service development. Results: Survey results, while not generalisable, highlight an urgent need for further investigation. Three themes were identified: Witnessing the end–of–life and family distress. Situations that mirror personal experience prompted reflection, discomfort and distress. Witnessing families' distress and grief reactions had substantial impact. This was more prevalent when families were unprepared, in denial, or lacking knowledge. Although ambiguous, witnessing a patient or family member of young age had an effect. Lack of services. Inadequate planning and poor provision of other health care services, particularly out–of–hours, resulted in a perceived lack of support for families. Difficulty accessing care for a patient to stay at home had an emotional impact. 'Supporting' family. The role of supporting families was emotionally burdensome. Responses suggested 'support' related to emotional, physical and providing information. Staff managed family expectations through explanation, information sharing and delivering bad news. These conversations had emotional consequences. Conclusions: Supporting unprepared families, difficulty accessing other services and resonating personal experiences all had an emotional impact. Actions to improve staff wellbeing and service development: Introduction of Schwartz Rounds to support emotional reflection; Pathway development with palliative care services to improve out–of–hours support; Education for line managers on providing bereavement support and developing communication skills for clinicians; Emotional resilience should be included within the end–of–life care curricula; Share results shared with the National Ambulance End–of–life Care Forum.